Stochastic potential ecological risk model for heavy metal contamination in sediment. (July 2019) - Feng, Yan; Bao, Qian; Yunpeng, Chen; Lizi, Zhao; Xiao, Xiao
Highlights: Potential ecological risk index ignores the uncertainty in the background. A new stochastic potential ecological risk model (SPERM) is established. SPERM has a better capacity in uncertainty analysis. Hg and Cd are the key risk indices of Eastern Dongting Lake. Abstract: Conventional potential ecological risk index (PERI) cannot address the uncertainty in the geochemical background of heavy metal. For a solution, a stochastic potential ecological risk model (SPERM) is established based on uncertainty analysis theory. SPERM uses the stochastic risk index to recognize the risk category and the stochastic risk vector to quantify the uncertainty in evaluation. SPERM is applied to ecological risk assessment in the sediment of Eastern Dongting Lake. Results show the following: (i) Compared with conventional PERI, SPERM has better capacity in addressing the uncertainty in geochemical background information and better capacity in grade reorganization. (ii) The major risk indices of Eastern Dongting Lake are mercury (Hg) and cadmium (Cd). In the sediment Xiang River estuary, both the potential ecological risk grades of Hg and Cd are "high;" and they have possibilities of 0.25 and 0.37 to deteriorate to the "very high" category, respectively. In the sediment of Xinqiang River estuary and the central part of Eastern Dongting Lake, the potential ecological risk grades of Hg and Cd are "considerable" and "very high, " respectively. Furthermore, the potential ecological risk of Cd in Xinqiang River estuary has a probability of 0.14 to deteriorate to "very high" grade.